2016
DOI: 10.1515/biol-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

The unusual yin-yang fashion of RIZ1/RIZ2 contributes to the progression of esophageal squamous cell carcinoma

Abstract: Retinoblastoma protein-interacting zinc finger gene RIZ encodes two different protein products, RIZ1 and RIZ2. Observations suggest that RIZ1 is a tumor suppressor, while RIZ2 acts as a negative regulator of RIZ1 and may play a positive role in oncogenesis. The imbalance amount of RIZ1 and RIZ2 may be involved in cancer development. In this study we detected the expression levels of RIZ1 and RIZ2 mRNA in human esophageal squamous cell carcinoma (ESCC) tissue specimens, reexpressed RIZ1 in the human ESCC cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The imbalance expression of RIZ1/RIZ2 contributes to the progression of ESCC. 18,19 The occurrence and development of ESCC is a complex process involving multiple factors, multiple genes changing and multiple stages of carcinogenesis. Mig-6 located in this region has tumor-inhibiting activity in a variety of malignant human cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imbalance expression of RIZ1/RIZ2 contributes to the progression of ESCC. 18,19 The occurrence and development of ESCC is a complex process involving multiple factors, multiple genes changing and multiple stages of carcinogenesis. Mig-6 located in this region has tumor-inhibiting activity in a variety of malignant human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The deactivation of RIZ1 was associated with highly methylation in DNA promoter region and could induce imbalance expression of RIZ1/RIZ2. The imbalance expression of RIZ1/RIZ2 contributes to the progression of ESCC 18,19 . The occurrence and development of ESCC is a complex process involving multiple factors, multiple genes changing and multiple stages of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, further research to identify novel biomarkers should be performed. thyroid carcinoma (Cheng et al 2010;Cui et al 2016;Johansson et al 2018;Lal et al 2006;Michalak & Visvader 2016;Oshimo et al 2004;Pandzic et al 2017;Rossi et al 2009;Sakurada et al 2001;Tan et al 2014;Wu et al 2016;Yang et al 2017;Zhang et al 2016). Furthermore, in a meta-analysis that found a total of 22 genes methylated in hepatocellular carcinoma, PRDM2 was one of the genes with the most significant result and is on par with the well-known APC and p16 (Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Its gene products are also involved in DNA-binding and transcription factor binding-activities, implicating its role in carcinogenesis (Sorrentino et al, 2018;Zhang et al, 2015). Studies have also reported PRDM2 downregulation in cancers that exhibit high incidence and mortality, such as bladder cancer, breast cancer, cervical cancer, colorectal cancer, endometrial cancer, esophageal squamous cell carcinoma, gastric carcinoma, hepatocellular carcinoma, lung cancer, pancreatic cancer, prostate cancer, T-cell prolymphocytic leukemia and thyroid carcinoma (Cheng, Gao & Lou, 2010;Cui et al, 2016;Johansson et al, 2018;Lal et al, 2006;Michalak & Visvader, 2016;Oshimo et al, 2004;Pandzic et al, 2017;Rossi et al, 2009;Sakurada et al, 2001;Tan et al, 2014;Wu et al, 2016;Yang et al, 2017;Zhang et al, 2016). Furthermore, in a meta-analysis that found a total of 22 genes methylated in hepatocellular carcinoma, PRDM2 was one of the genes with the most significant result and is on par with the well-known APC and p16 (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%